Barriers and facilitators to change in the organisation and delivery of endoscopy services in England and Wales: a focus group study. Issue 3 (25th June 2012) - Rapport, Frances; Seagrove, Anne C; Hutchings, Hayley A; Russell, Ian T; Cheung, Ivy; Williams, John G; Cohen, David
Abstract : Objective: Explore professional views of changes to gastroenterology service organisation and delivery and barriers and facilitators impacting on change. The work was undertaken as part of an evaluation in endoscopy service provision catalysed by the Modernising Endoscopy Services Programme of the Modernisation Agency. Design: Focus groups followed by analysis and group-working activities identifying key themes. Setting: English and Welsh s econdary care gastroenterology units. Participants: 20 professionals working in gastroenterology in England and Wales. Medical, surgical and nursing specialists including endoscopy nurses. Opportunistic sampling to include senior people in leadership and management roles who were directly involved in service modernisation, excluding those involved in the Modernisation Endoscopy Services Programme. Results: Four 1.5 h focus groups took place in 2007. Summative and thematic analyses captured essential aspects of text and achieved consensus on key themes. 4 themes were revealed: 'loss of personal autonomy and erosion of professionalism', 'lack of senior management understanding', 'barriers and facilitators to change' and 'differences between English and Welsh units'. Themes indicated that low staff morale, lack of funding and senior management support were barriers to effective change. Limitations to the study include the disproportionately low number of focus group attendees from English units and the time delay in reporting these findings. Conclusions: Despite ambitions to implement change, ineffective management support continued to hamper modernisation of service organisation and delivery. While the National Health Service Modernisation Agency Modernising Endoscopy Services Programme acted as a catalyst for change, affecting the way staff work, communicate and think, it was not effective in heralding change itself. However, gastroenterologists were keen to consider the potential for change and future service modernisation. The methodological framework of innovative qualitative enquiry offers comprehensive and rigorous enhancement of quantitative studies, including randomised trials, when a mixed methods approach is needed.